IMPLEMENTASI PRINSIP KONSTITUSIONAL DALAM REGULASI KEAMANAN STRUKTURAL BANGUNAN GEDUNG: KAJIAN YURIDIS, NORMATIF, DAN TEKNIS - Parabi, Ashraf Dhowian; Aisyah, Siti; Serera, Aulia Yuti; Yuliana; Mukti, Plasma Versiana; Octaviyana, Rickhy Artha (Jurnal Teknologi Infrastruktur, 2025)
This study critically analyzes the implementation of constitutional principles within the framework of structural safety regulations for building constructions in Indonesia. The intersection between constitutional law and civil engineering becomes urgent to analyze considering the significant transformation of building construction regulations following the enactment of the Job Creation Law (Law No. 11 of 2020) and Government Regulation No. 16 of 2021. The study employs a normative juridical approach integrated with technical analysis through doctrinal legal research methods while still considering empirical aspects of structural safety standards. Through legislative, conceptual, and comparative approaches, this study identifies significant implementation gaps between constitutional principles and structural safety technical standards. The results indicate that: (1) there is disharmony between constitutional principles and the implementation of technical regulations, especially in the aspect of protecting citizens' human rights; (2) the paradigm shift from Building Permit (IMB) to Building Approval (PBG) has not fully accommodated the fulfillment of constitutional rights of building users; and (3) the state's constitutional accountability mechanism in building failures remains weak. The study recommends reformulating structural safety regulations that integrate constitutional principles with technical standards by strengthening the state's responsibility dimension in ensuring building safety, as well as improving the Building Feasibility Certificate (SLF) mechanism as a constitutional protection instrument. Keywords: Building construction, normative juridical study, job creation law